Pendampingan Pengolahan Limbah Kotoran Kelinci di Desa Pomahan - Pernama, Candra; Setyowati, Nanik (Social Science Academic, 2025)
The purpose of this research is to increase the desire of the community in pomahan village to utilize rabbit solid and liquid manure as fertilizer on plants cultivated in the community. the result of this service is that proper handling is needed to overcome the waste problem. This method uses qualitative with an ABCD (Asset based community devlovmen) approach that emphasizes empowerment, understanding of the potential and challenges possessed to improve the quality of individuals and groups of objects of this service to the community, especially rabbit livestock with the implementation of a community service program in order to utilize rabbit waste solid and liquid organic fertilizer derived from rabbit droppings. the use of rabbit droppings can be as solid and liquid organic fertilizer can provide additional knowledge for rabbit breeders. Rabbit farmers also get information about the quality of rabbit manure waste and mixed waste and their impact on the fertility of agricultural land. the conclusion of this service is that rabbit manure waste can be reprocessed and used as organic fertilizer so that it is environmentally friendly and does not cause odors in the community.